Board Faultlines, Innovation Strategy Decisions, and Faultline Activation: Research on Technology-Intensive Enterprises in Chinese A-Share Companies - Zhang, Yan; Ma, Lianfu (Frontiers in Psychology, 2022)
In the context of social norms, based on faultline theory, using samples of Chinese A-share listed companies of technology-intensive industries from 2009 to 2015, this paper studies how board faultlines influence innovation strategy decisions and test the influences of a dual chairman/CEO and board ownership on that relationship. The results of the study are as follows. Social-related faultlines have a significant negative influence on innovation strategy decisions. Cognitive-related faultlines have a significant positive influence on innovation strategy decisions. A dual chairman/CEO has no moderating effect between social-related faultlines and innovation strategy decisions, but weakens the positive effect between cognitive-related faultlines and innovation strategy decisions. Board ownership weakens the negative effect between social-related faultlines and innovation strategy decisions but enhances the positive effect between cognitive-related faultlines and innovation strategy decisions.